Identificación y elaboración de productos turistícos del cantón Salcedo. - Rivera Palomo, Johana Alexandra (2023)
The present research aimed at the development of tourist products of the Salcedo canton taking into account the natural attractions it has, which is why an analysis of the territory was carried out where it was known that the canton is a city of passage, the scarce tourist information, the lack of products and the lack of promotion and tourist dissemination in the different parishes of the canton. In order to design these products, the areas least visited by tourists have been considered and for the promotion the University Tourism Center was taken into account, which is a project linking the Tourism Career. The research has a qualitative approach, with descriptive, exploratory, inductive method, 3 objectives have been developed; in objective 1 the inventory of natural tourist attractions was validated where a bibliographic review of the PDOT was developed to know the situation in which the territory is located, the field trip was carried out for the verification of the list of natural attractions and through the methodology of the MINTUR the check list was developed taking into account the parameters of said methodology, as a result there were 14 natural tourist attractions of the Salcedo canton and 2 attractions that have currently become resources due to the lack of care and maintenance, in this way the updated database was obtained. Objective 2 designed two tourism products called "Hidden Adventures of Salcedo" and "Touring the viewpoints" For this, 7 natural attractions of the communities of San Diego, Laguamasa, Palama, Papahurco, the Patain neighborhood and Panzaleo were taken into account, for the design was carried out through the steps of the Planning Manual of Tourism Products of Peru, The analysis of the destination was developed where information was obtained about the reality of the canton, for the offer it was based on the activities, attractions, tourist services within the territory, in the demand the profile of the tourist was obtained resulting in; tourists from 18 to 50 years old who visit the Llanganates National Park and the Yambo Lagoon, as a result tourist products were obtained designed with their respective natural attractions, activities, tourist services that are within the product, in addition the route was made where each product will be made in the canton, the budget to pay in the different products goes from $ 40 to 60 dollars that includes the above. In objective 3 it was carried out with the tools of the focus group that allowed to develop theSWOT based on the promotion and tourist diffusion of the canton, later MEFE and MEFI evaluation matrices were elaborated to obtain as a result promotion and dissemination strategies such as an offensive promotion strategy through web pages and videos, A defensive to establish a marketing plan, a survival to design a tourist brand of the canton and an adaptation to carry out talks and training based on tourism and translate them into the proposal of the action plan.